THE DEGREE OF PATIENT SATISFACTION AND THE FREQUENCY OF COMPLICATIONS AFTER THE INSTALLATION OF PARTIAL REMOVABLE PROSTHESES - Gubaev Mukhitdin Sarimsokovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Tooth loss can negatively affect the aesthetics of the face, affect the functions of speech and chewing. Removable prosthetics is a common type of treatment for partial adentia. Based on the physiological, anatomical and psychological needs of the patient, diagnosis and subsequent manufacture of a dental prosthesis can significantly improve the quality of life of patients and positively affect the life expectancy of the elderly population. Nevertheless, some patients are dissatisfied after the treatment and cannot use their removable prostheses. The most common problems include increased salivation in the first 72 hours, pain and discomfort, as well as lack of stability and retention.